Research on the Core Competitive Power Elements Evaluation System of Green Hotel - Liang, Hui (Journal of Economic Development, Environment and People, 2013)
Green hotel is a new type of hospitality industry development model based on the concept of circular economy and sustainable development. This paper makes an analysis and evaluation of the elements of green hotel core competence, on this basis, constructs the Green Hotel core competitive evaluation index system.The construction of the system is conducive to understand the green hotel’s own competitive advantage objectively, and explore ways to enhance its core competitiveness, providing objective basis for sustainable development of China’s Hotel industry.